Development of an optimum pre-founded column system for top-down construction - Rhim, Hong-Chul; Kim, Kyung-Min; Kim, Seung-Weon (Journal of Civil Engineering and Management, 2012)
In this work, circular concrete-filled steel tubular (CCFT) columns, rather than the more popular H-shaped columns, were suggested as pre-founded columns for top-down construction. In addition, a novel shear connection system with headed stud shear connectors between the CCFT columns and the flat slabs was developed. It was noted that a CCFT column with a design compressive strength similar to that of an H-shaped column without consideration of length effects can be easily installed, even into a smaller borehole. Furthermore, compared to the H-shaped column, less steel is required for the CCFT column. It was shown that the amount of steel needed can be reduced by decreasing the wall thicknesses or diameters of the CCFT column depending on the exposed length of the column during excavation. The fillet-welded joint of the developed shear connector system was also tested before its in-situ application. The test results revealed that the joint possessed sufficient shear and deformation capacities. The CCFT column with the developed shear connection system was ultimately applied to an actual top-down construction process. The good constructability of the CCFT column system and reductions in construction costs and time were confirmed.